Підходи до вибору моделі ринкової економіки України - Яковенко, Р. В.; Yakovenko, R. (Кропивницький : сайт www.surma-ua, 2018)
У статті визначено спільні риси усіх національних економік та критерії формування ефективної моделі економіки України. The article defines the common features of all national economies and criteria for the formation of an effective economy model of Ukraine.
Approaches to choosing a model of a market economy in Ukraine
Keywords: економічна система; лібералізація; ринкова економіка; досвід; приватна власність; валюта; право; economic system; liberalization; market economy; experience; private property; currency; law